Open Innovation as Means of Building Social Capital: A Way to Globalization for Traditional SMEs - Phillips, Jenny Oliveros Lao (Journal of Strategic Innovation and Sustainability, 2018)
This research explores innovation of traditional SMEs that do not actively invest in innovation. Elements of open innovation have been identified in these firms in their effort to build social capital which they perceive as pertinent to their businesses. The result of the research shows that instead of using social capital as means for innovation, the unintentional practice of open innovation has contributed to the development of social capital, which further opens up potential for globalization. As a result, a model of open innovation as means of developing social capital for enhancing globalization potential for SMEs was developed.